Inequality and the impact of growth on poverty: Comparative evidence for Sub-Saharan Africa - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This study explores the extent to which inequality affects the impact of income growth on the rates of poverty changes in sub-Saharan Africa (SSA) comparatively with non-SSA, based on a global sample of 1977-2004 unbalanced panel data. For both regions and all three measures of poverty - headcount, gap, and squared gap - the paper finds the impact of GDP growth on poverty reduction as a decreasing function of initial inequality. The impacts are similar in direction for SSA and non-SSA, so that within both regions there are considerable disparities in the responsiveness of poverty to income growth, depending on inequality. Nevertheless, the income-growth elasticity is substantially less for SSA, implying relatively small poverty-reduction sensitiveness to growth compared with the rest of the developing world. Furthermore, the paper finds a considerable variation in the predicted values of the income-growth elasticity across a large number of SSA countries, implying the need for understanding country-specific inequality attributes for effective poverty-reduction strategies.
Keywords: D31; I32; O49; 330; inequality; income growth; poverty; sub-Saharan Africa; Einkommensverteilung; Armut; Sozialprodukt; Afrika südlich der Sahara